A near-infrared fluorescent probe for monitoring viscosity in living cells, zebrafish and mice. (18th February 2021) - Zhan, Jingting; Geng, Chen; Hao, Xinya; Song, Wenhui; Lin, Weiying
Abstract : A novel NIF fluorescent probe, ZM-V, was designed, in which interior imidazole and benzopyrene moieties serve as rotators, which can spin around multiple C–C bonds in the conjugated skeleton. Abstract : A novel NIF fluorescent probe, ZM-V, was designed, in which interior imidazole and benzopyrene moieties serve as rotators, which can spin around multiple C–C bonds in the conjugated skeleton. The fluorescence intensity of ZM-V changed 111-fold from water to glycerol, displaying significant red-fluorescence enhancement with an emission at 666 nm. Furthermore, ZM-V exhibited a large Stokes shift of 166 nm. Co-staining tests proved that ZM-V could target the mitochondria with a high Pearson's correlation coefficient of 0.94, and detect changes in mitochondrial viscosity. Notably, ZM-V was also successfully used to monitor viscosity variations in zebrafish and mice due its superior properties.